"Their duty to God and Man": religion in eighteenth- and nineteenth-century children's dictionaries - Iversen, S (2010)
The 'children's dictionary' has been widely regarded as a twentieth-century phenomenon. My thesis, however, argues that children's dictionaries existed as early as the eighteenth- and nineteenth centuries. Dictionaries addressed to children in this time were not simply miniature adult dictionaries, but works stylistically and ideologically geared towards a juvenile audience. This paper explores one facet of ideological adaptation of children's dictionaries in the period 1750-1870, namely religious education. Before elementary education was made compulsory and secular with the 1870 Education Act, all education was fundamentally religious and moral and religious edification was regarded as being at least as important as academic instruction. Whether or not children should receive a Christian education was not the issue, but there was strong disagreement as to the nature of this edification. As didactic works in a religiously divided society, children's dictionaries reflected, and indeed, carried out such disagreements. The wordings of definitions and choices of headwords within these works were not simply guided by limitations of space, or by ideas about children's intellectual capabilities, but also by the lexicographers' religious and ethical views. This paper considers the pervasiveness of religion within children's dictionaries, both in terms of establishing a religious norm against which other beliefs were judged, and in terms of inculcating children with the precepts of the 'true' religion. Focusing particularly on the treatment of, and discrimination against, Roman Catholics, but also on other religions, this paper examines religious bias and moral-religious prescriptivism in definitions, illustrative examples and pictorial illustrations.